Transition to online learning by a teacher education program with limited 4IR affordances - Maria Tsakeni (Research in Social Sciences and Technology, 2021)
This study used the community of inquiry (CoI) framework and the affordances of Internet of things (IoT) to explore how the faculty of education of a rural campus of a university transitioned from face-to-face to online modes of instruction. In this qualitative interpretive study, data were collected through open-ended questionnaires from four purposely selected teacher educators and five final-year bachelor of education preservice teachers. Thematic content analysis techniques were used to analyze the data collected. The findings indicated the tensions experienced by the teacher educators as they negotiated the limited IoT affordances to ensure effective teaching, cognitive, and social presence in the newly formed online classrooms. Some of the tensions included the choices that were made on whether to use synchronous or asynchronous modes of instruction and the selection of effective communication modes. The teacher educators used a combination of the official learning management system (LMS) tools of the university and a social media platform as way of navigating the limited 4IR environments experienced by the preservice teachers.